Relation between quality and rheological properties of lactic beverages - Penna, ALB; Sivieri, K.; Oliveira, M. N. (Elsevier B.V., 2001)
The physicochemical (pH, fat and total solids content), sensory (appearance, consistency and taste), and rheological characteristics of five different commercial brands of lactic beverages were determined. Rheological measurements were obtained at 5 degreesC and 25 degreesC using a Brookfield rheometer. The experimental data were described by the power law and Herschel-Bulkley models. The ANOVA of the results were conducted using an incomplete block design, and using Tukey test. Samples showed a significant difference (P less than or equal to 0.05%) for fat content and pH. There was a significant difference in total solids content only among Nestle (A), Batavo (C), and Parmalat (D) samples. Sensory evaluation showed more global acceptability for Nestle; however, Nestle and Vigor (E) lactic beverages obtained better results for appearance than for consistency and taste. Batavo obtained the best score for taste. All test samples exhibited non-Newtonian behavior, with thixotropy. Upward curves showed pseudoplastic behavior, while downward curves showed dilatant behavior with the exception of the Nestle sample, at 25 degreesC. Lactic beverages from all brands analyzed showed similar rheological behavior. (C) 2001 Elsevier B.V. Ltd. All rights reserved.
Keywords: yogurt; lactic beverage; Rheology; quality